Inventarisasi, Keanekaragaman Fish Inventory in the Cikaniki Area of Mount Halimun Salak National Park: Inventarisasi Ikan di Kawasan Sungai Citalahab Desa Cikaniki Taman Nasional Gunung Halimun Salak - Evifa Lutfiah Sya'bani Choirunisa; Tafrijiyah Hasanah; Intan Aliyani; Nanda Nur Aliza; Egi Sudira; Arikah Putri Afriani; Oktantia Almira Putri; Adinda Zhafarah Fathiyyah; Hanum Isfaeni; Rizka Malintan (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2025)
Indonesia has high biodiversity, making it the country with the second largest biodiversity in the world. To preserve this wealth, the government has established conservation areas, including the Gunung Halimun National Park in West Java, which is the largest tropical rainforest on the island of Java with unique flora and fauna. This research was carried out in the Citalahab River, part of the national park, to identify the fish species present. Sampling used a purposive sampling method, and fish species were identified based on data from gbif.org, fishbase.org, as well as the latest literature. The results of the research show that there are seven species of fish in the Cikaniki area, namely Puntius sp. (wader fish), Channa sp. (snakehead fish), Xiphophorus sp. (swordtail fish), Glyptothorax sp. (kekhel fish), Gambusia sp. (cere fish), Rasbora sp. (spray fish), and Monopterus sp. (field eel). Each species is described based on its morphological characters and habitat. These results emphasize the importance of conserving natural river habitats, because species diversity plays an important role in maintaining ecosystem stability and ecological balance.